The fractionation of woody biomass under mild conditions using bifunctional phenol-4-sulfonic acid as a catalyst and lignin solvent. Issue 16 (29th July 2020) - He, Duo; Wang, Yunxuan; Yoo, Chang Geun; Chen, Qi-Jie; Yang, Qiang
Abstract : The lignin-derivable bifunctional phenol-4-sulfonic acid as a catalyst and lignin solvent can near-completely fractionate woody biomass at mild conditions. Abstract : The complete and mild-condition fractionation of woody biomass without energy-intensive size reduction still remains a significant challenge. This study reports an innovative cellulose-centred fractionation process based on bifunctional, recyclable, inexpensive, and lignin-derivable phenol-4-sulfonic acid (PSA). The results showed that aqueous PSA solution ( e.g., 72 wt%) near-completely fractionated centimetre-sized hardwood, such as poplar and birch chips, into cellulose fibres of high quality (length: >1 mm, crystallinity index: 61–65, DPv : 830–887), fermentable hemicellulose sugars, and lignin in theoretical maximum yields under mild conditions ( e.g., 50–80 °C, 0.5–3 h, atm). Calculations and experimental results suggest that PSA, as a small amphiphile, could form aggregates and clusters in water. Therefore, during fractionation, PSA acted as not only a selective catalyst through the immobilized sulfonic acid groups to depolymerize hemicellulose and lignin, but also as a mesoscale solvent to solubilize and protect lignin fragments through aggregates and accumulating around them due to the hydrophobic effect.